Structural and magnetic properties of Ni/Pt multilayers - Quiroga, Matías Abel Oscar (2007)
In this work, the variation of the magnetic moments of the Ni/Pt multilayers are studied using the linearized augmented plane waves (LAPW) method in the framework of the density functional theory (DFT) implemented in the version of WIEN2K program. The systems have been modeled by seven layers slab separated in z direction by a vacuum region of four substrate layers. We present the results of the dependence of the magnetic properties with respect to the thickness variation of the different multilayers. The modeling of these systems finds an important empirical support. Experiment and theory show the same trends for the magnetic moments: hybridization effects between Ni and Pt are mostly localized at the interface.